Sustainable investing in the US and European insurance industry: a text mining analysis - Nadine Gatzert; Philipp Reichel (The Geneva Papers on Risk and Insurance - Issues and Practice, 2022)
This paper uses a text mining analysis to study the development of sustainable investing in the European and US insurance industry as reflected in their public reports from 2013 to 2018. The sample comprises 1215 annual, sustainability- and investment-related documents of 77 firms. We develop a dictionary with principles, criteria and terminologies as well as strategies, and differentiate between the quality of reports. Our results show that the number of firms referring to as well as the word count related to sustainable investing substantially increase over the sample period, and that insurers reporting about sustainable investing are on average significantly larger. We also find that European insurers report much more extensively on their sustainable investment practices as compared to US insurers in our sample. Most relevant in 2018 are references to general ESG criteria, followed by responsible investment and the Sustainable Development Goals . Top strategies mentioned were ESG integration and impact investing , whereby we observe that insurers evolve from mentioning one single towards multiple strategies over time. Finally, a regression analysis does not show a value-effect of sustainable investment-related keywords in reporting on Tobin's Q, which may be due to the rather long-term investment perspective.
Keywords: 330; Sustainable investing; Environmental; social and governance (ESG); Text mining